1999
DOI: 10.1097/00007435-199908000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Trichomonas vaginalis As a Cause of Urethritis in Malawian Men

Abstract: T. vaginalis was detected in 51 of 293 men. The estimated prevalence among symptomatic men was 20.8% and among asymptomatic men, 12.2%. Polymerase chain reaction performed with a sensitivity of 0.82 (95% CI: 0.66-0.92) and specificity of 0.95 (95% CI: 0.91-0.97) compared to wet-mount microscopy and culture. There was no difference in the rate of HIV seropositivity in men with and without T. vaginalis infection. However, in men with symptomatic urethritis, the median HIV RNA concentration in seminal plasma from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(99 citation statements)
references
References 20 publications
7
91
1
Order By: Relevance
“…vaginalis have been shown to have a higher seminal viral load than those with either T. vaginalis negative, or with an asymptomatic (Hobbs et al, 1999). Those with symptoms of urethritis will necessarily have the greatest level of inflammation, and the greatest levels of CD4 lymphocytes and macrophages, increasing the targets for HIV invasion.…”
Section: Relationship With Other Microorganismsmentioning
confidence: 99%
“…vaginalis have been shown to have a higher seminal viral load than those with either T. vaginalis negative, or with an asymptomatic (Hobbs et al, 1999). Those with symptoms of urethritis will necessarily have the greatest level of inflammation, and the greatest levels of CD4 lymphocytes and macrophages, increasing the targets for HIV invasion.…”
Section: Relationship With Other Microorganismsmentioning
confidence: 99%
“…13,15,20,24,[48][49][50] Other risk factors for TV infection include: illicit drug use, tobacco use, incarceration, prostitution, vaginal douching, intact foreskin, vaginitis, and concurrent STIs. 3,7,13,14,18,26,30,36,37 Given the identified risk factors and at risk populations, it is in the hands of health care providers to embrace screening and treatment of TV infections. The evidence supporting increased risk of HIV acquisition and transmission in patients with TV infection is substantial.…”
Section: Infectious Diseasementioning
confidence: 99%
“…11,30,32,35 Male and female patients infected with TV demonstrate increased rates of genital HIV shedding. 15,19,26,28,36 This may result from TV inducing TNF-α, which increases the rate of HIV replication. 2 Treatment of TV in HIV positive men and women decreases genital shedding, but the response is delayed over a period of up to 3 weeks following therapy, possibly due to the robust inflammatory response associated with TV infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infection in majority of the males is asymptomatic and it has been suggested to be very important in nongonococcal and non-chlamydial urethritis (Krieger et al, 1993). Study has shown that men with symptomatic Trichomonas urethritis were found to have increased HIV concentrations in seminal plasma compared to HIV infected men without urethritis (Hobbs et al, 1999). Moreover, the acquisition of Human Immunodeficiency Virus has been associated with trichomoniasis in several studies conducted in Africa (Laga et al, 1993, Buve et al, 2001, meaning the organism needs to be taken seriously.…”
Section: Introductionmentioning
confidence: 99%